Wybrane zachowania zdrowotne oraz czynniki ryzyka raka piersi w grupie pielęgniarek województwa lubelskiego i podkarpackiego = Selected health behaviours and risk factors of breast cancer in nurses group from Lublin and Subcarpathian provinces - Ewa Smoleń; Beata Dobrowolska (Kazimierz Wielki University, 2016)
Smoleń Ewa, Dobrowolska Beata. Wybrane zachowania zdrowotne oraz czynniki ryzyka raka piersi w grupie pielęgniarek województwa lubelskiego i podkarpackiego = Selected health behaviours and risk factors of breast cancer in nurses group from Lublin and Subcarpathian provinces. Journal of Education, Health and Sport. 2016;6(7):346-358. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.57969 http://ojs.ukw.edu.pl/index.php/johs/article/view/3697       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.06.2016. Revised 09.07.2016. Accepted: 09.07.2016.     Wybrane zachowania zdrowotne oraz czynniki ryzyka raka piersi w grupie pielęgniarek województwa lubelskiego i podkarpackiego   Selected health behaviours and risk factors of breast cancer in nurses group from Lublin and Subcarpathian provinces   Ewa Smoleń1, Beata Dobrowolska2   1Zakład Pielęgniarstwa, Instytut Medyczny, Państwowa Wyższa Szkoła Zawodowa im. J. Grodka w Sanoku Jan Grodek State Higher Vocational School in Sanok, Medical Institute, Department of Nursing, Sanok   2Katedra Rozwoju Pielęgniarstwa, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie Department of Development in Nursing, Faculty of Health Sciences, Medical University, Lublin   Słowa kluczowe: rak piersi, zapobieganie, ryzyko zachorowania, pielęgniarki. Key words: breast cancer, prevention, risk, nurses.   Streszczenie Wstęp. Do najważniejszych czynników ryzyka zachorowania na raka piersi zalicza się: płeć żeńską, wiek powyżej 64 r.ż., mutacje genowe, rozpoznanie nowotworu piersi u dwóch lub więcej krewnych I stopnia, przebyty rak piersi oraz zmiany w piersi. W profilaktyce raka piersi ważne znaczenie obok badań przesiewowych ma podejmowanie prozdrowotnych zachowań zdrowotnych, zmniejszających ryzyko zachorowania. Cel pracy. Ocena zachowań zdrowotnych pielęgniarek w zakresie profilaktyki raka piersi oraz ryzyka rozwoju chorób nowotworowych w badanej grupie kobiet. Materiał i metody. Badania przeprowadzono metodą sondażu diagnostycznego w grupie 184 pielęgniarek województwa lubelskiego i podkarpackiego. Zastosowano kwestionariusz ankiety własnej konstrukcji. W analizie statystycznej posłużono się testem χ2 Pearsona. Wyniki. U ponad połowy respondentek w rodzinie notowano wystąpienie nowotworu, a u co dziesiątej był to nowotwór piersi. Jedna dziesiąta pielęgniarek deklarowała rozpoczęcie miesiączkowania w 12 r.ż. Większość pielęgniarek deklarowała karmienie naturalne w okresie macierzyństwa. Średnia wieku pierwszej wizyty u ginekologa to 20 lat. Ponad połowa badanych pielęgniarek deklarowała prawidłową masę ciała oraz podejmowanie aktywności fizycznej. Wykazano niewielkie różnice istotne statystycznie w poszczególnych zachowaniach w obu badanych grupach pielęgniarek. Wnioski. Zagrożenie wystąpieniem nowotworów piersi u badanych pielęgniarek związane było w głównej mierze z rodzinnym obciążeniem nowotworowym oraz wczesnym rozpoczęciem menstruacji, co zalicza się do czynników niepodlegających modyfikacji. Brak aktywności fizycznej oraz występowanie otyłości to czynniki ryzyka modyfikowalne, których intensyfikację można zmniejszyć poprzez zmianę stylu życia na prozdrowotny.     Abstract Introduction. The most important risk factors of breast cancer include: female gender, age over 64 years, gene mutations, the diagnosis of breast cancer in two or more first degree relatives, previous breast cancer and changes in the breast. Besides screening, health behaviours reducing the risk of breast cancer are significant in its prevention. Aim. Assessment of health behaviours of nurses in the scope of prevention of breast cancer and risk factors of cancer development in women surveyed. Material and methods. The diagnostic survey with the use of self-constructed questionnaire was applied in the study. The survey was carried out in the group of 184 nurses from Lublin and Subcapathian provinces. Test χ2 was utilized in the statistical analysis. Results. Over half of surveyed group reported occurrence of cancer in their family, and in every tenth cases it was breast cancer. The one tenth of nurses declared that they started their menstruation in 12 years of age. Most of nurses declared breastfeeding in their maternity period. The average age of respondents of their first visit in gynaecologist was 20. More than half of nurses surveyed declared correct body weight and physical activity. Slight statistical differences were shown in individual behaviours of nurses from two provinces.    Conclusions. The threat of the occurrence of breast cancer in the group of examined nurses was associated primarily with the cancer recorded in the family and the early start of menstruation, which is one of the unmodifiable factors. Physical inactivity and obesity are modifiable risk factors which intensity can be reduced by changing lifestyle.